Innovative molecular targets for combatting metastasis in adrenocortical carcinoma - Kong, Jianqiu; Chen, Xiong; Fan, Xinxiang; Fang, Shuogui; Zhang, Qihang; Zhang, Long; Liao, Chenxiao; He, Qingqing; Xie, Weibin; Xing, Yichun; Zheng, Junjiong (Frontiers in Endocrinology, 2025)
BackgroundMetastasis in adrenocortical carcinoma (ACC) presents a formidable clinical challenge, with limited insights into its underlying mechanisms and few effective treatment options. This study aimed to identify molecular markers associated with metastasis in adult ACC and to explore novel therapeutic approaches.MethodsRNA sequencing data from 74 adult ACC patients were analyzed using bioinformatics approaches, including weighted gene co-expression network analysis (WGCNA) and differential gene expression analysis. Functional pathway enrichment analyses were conducted to identify metastasis-associated genes and to explore key biological pathways contributing to metastatic progression. Candidate genes were selected based on their statistical significance, prognostic relevance, and involvement in metastatic processes.ResultsSeven hub genes were identified as significantly associated with metastasis and poor prognosis in ACC patients. These genes were enriched in pathways critical to tumor progression, such as mismatch repair, nucleotide excision repair, and cell cycle regulation. High expression levels of these genes correlated with reduced overall survival. Importantly, potential therapeutic agents targeting these molecular drivers were identified, offering promising, lower-toxicity options for treating metastatic ACC.ConclusionThe molecular markers identified in this study offer valuable insights into the mechanisms underlying ACC metastasis and represent promising therapeutic targets, providing a foundation for developing improved treatment strategies in clinical practice.